1998
DOI: 10.1097/00000542-199803000-00030
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia Sensitivity in Mice that Lack the β3 Subunit of the γ-Aminobutyric Acid Type A Receptor 

Abstract: The beta3 subunit of the GABA(A) receptor appears to be important in the mediation of the immobilizing (tail clamp) but not obtunding (loss-of-righting reflex) effects of the volatile anesthetic agents enflurane and halothane. These data support the hypotheses that separate components of the anesthetic state are mediated via different central nervous system loci; that the GABA(A) receptor is a likely target for the immobilizing response to volatile anesthetic agents; and that the beta3 subunit plays a direct o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
53
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(59 citation statements)
references
References 22 publications
4
53
1
1
Order By: Relevance
“…To extend previous evidence of 6Ј tryptophan substitutions blocking alcohol inhibition of ␣2␤2 GABA A Rs (Ueno et al, 2000), we examined the effect of n-alcohols and volatile anesthetics on GABA A Rs of the same composition (␣2␤2) containing the tryptophan substitution ␣2(T6ЈW). Because GABA A Rs are implicated in immobilizing effects of n-alcohols and volatile anesthetics (Quinlan et al, 1998), we initially tested alcohol and anesthetic concentrations previously shown to produce 50% immobility (Alifimoff et al, 1989). Compared with wild-type receptors, tryptophan mutants showed greater enhancement by methanol and ethanol, but not by propanol, butanol, pentanol, hexanol, isoflurane, or chloroform (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To extend previous evidence of 6Ј tryptophan substitutions blocking alcohol inhibition of ␣2␤2 GABA A Rs (Ueno et al, 2000), we examined the effect of n-alcohols and volatile anesthetics on GABA A Rs of the same composition (␣2␤2) containing the tryptophan substitution ␣2(T6ЈW). Because GABA A Rs are implicated in immobilizing effects of n-alcohols and volatile anesthetics (Quinlan et al, 1998), we initially tested alcohol and anesthetic concentrations previously shown to produce 50% immobility (Alifimoff et al, 1989). Compared with wild-type receptors, tryptophan mutants showed greater enhancement by methanol and ethanol, but not by propanol, butanol, pentanol, hexanol, isoflurane, or chloroform (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, deletion of another ␤ subunit, ␤ 3 , also failed to change pentobarbital sleep time (Quinlan et al, 1998). Pentobarbital has effects on a number of other ion channels (Wartenberg et al, 2001;Yamakura et al, 2001;Bachmann et al, 2002), and it is possible that these targets are more important for pentobarbital-induced loss of righting reflex than the GABA A receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Mice lacking the ␥ 2 subunit die shortly after birth (Gunther et al, 1995), whereas mice deficient the ␥ 2L (long splice variant) subunit are viable and show small increases in sleep time responses to midazolam and zolpidem, but responses to nonbenzodiazepine agents such as ethanol, etomidate, and pentobarbital are unchanged (Quinlan et al, 2000). ␤ 3 null mice (Ϫ/Ϫ) did not show any changes in sleep times after administration of pentobarbital or ethanol, but they were more resistant to etomidate and midazolam (Quinlan et al, 1998). Mice lacking the ␣ 6 subunit of the GABA A receptor, which is expressed exclusively in cerebellar granule cells, have no major phenotypic abnormalities (Jones et al, 1997).…”
mentioning
confidence: 99%
“…However, subsequent testing with other neuronal depressants put into doubt whether the genes being selected specifically modulated anesthetic action (20). Knockout mice thus far have not revealed a predominant effect of any one gene on VA sensitivity (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Most notably, the knocking out of GABA A receptor subunits produced no or only small changes in VA sensitivity (21,23,25).…”
mentioning
confidence: 99%